a → 1 lim ( ln a 1 − a − 1 1 )
Find the value of the closed form of the above limit.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L = lim a → 1 ( ln ( a ) 1 − a − 1 1 ) = lim a → 1 ln ( a ) ( a − 1 ) a − 1 − ln ( a ) Putting a = 1, we get an indeterminate form 0 0 So, by L’Hospital’s rule L = lim a → 1 1 − a 1 + ln ( a ) a a − 1 Even now we have an indeterminate form 0 0 Again using L’Hospital’s rule L = lim a → 1 a 2 a + 1 a 2 1 = a + 1 1 Now substitute a = 1 L = 1 + 1 1 = 2 1 = 0 . 5
This is a good start. However, your explanation has an error.
Your solution has a simple fix. Do you see it?
Log in to reply
Oh yeah, it's not 1/0. Thanks I'll edit when am in my PC
Firstly let a = h+1
Our limit becomes 1/ln(h+1) - 1/h
Use Maclaurin's series for ln(1+x) now
Limit becomes
Can you fill in more details? How does using the Maclaurin series help directly? Seems like there are a few more steps to complete the solution.
If you think about it, in order to figure out the McLaurin series, you first have to find the value of this limit, not the other way around..
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: L'Hopital's Rule - Basic
L = a → 1 lim ( ln a 1 − a − 1 1 ) = a → 1 lim ln a ( a − 1 ) a − 1 − ln a = a → 1 lim a a − 1 + ln a 1 − a 1 = a → 1 lim a − 1 + a ln a a − 1 = a → 1 lim 1 + a a + ln a 1 = 2 1 = 0 . 5 This is a 0/0 case and L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t x Again 0/0 case. Differentiate up and down w.r.t x